Formulaicity as the Basis for Plot Construction in the Novels of Lydia Charskaya - Ryzhikh T. I. (History of culture, study of art and philology: modern points of view, 2021)
The article examines the work of Lydia Charskaya in the context of mass literature, the inherent prose of the writer’s formula and its relation to the gendered character characteristics.
Keywords: детская литература; массовая литература; женская литература; формульность; построение сюжета; Лидия Чарская; Children’s Literature; Mass Literature; Women’s Literature; Formula; Story Making; Lydia Charskaya